The performance of AI in medical examinations: an exploration of ChatGPT in ultrasound medical education - Hong, Dao-Rong; Huang, Chun-Yan (Frontiers in Medicine, 2024)
Objective: This study aims to evaluate the accuracy of ChatGPT in the context of China's Intermediate Professional Technical Qualification Examination for Ultrasound Medicine, exploring its potential role in ultrasound medical education.Methods: A total of 100 questions, comprising 70 single-choice and 30 multiple-choice questions, were selected from the examination's question bank.These questions were categorized into four groups: basic knowledge, relevant clinical knowledge, professional knowledge, and professional practice. ChatGPT versions 3.5 and 4.0 were tested, and accuracy was measured based on the proportion of correct answers for each version.Results: ChatGPT 3.5 achieved an accuracy of 35.7% for single-choice and 30.0% for multiple-choice questions, while version 4.0 improved to 61.4% and 50.0%, respectively. Both versions performed better in basic knowledge questions but showed limitations in professional practice-related questions. Version 4.0 demonstrated significant improvements across all categories compared to version 3.5, but it still underperformed when compared to resident doctors in certain areas.While ChatGPT did not meet the passing criteria for the Intermediate